Increased incidence of melanoma in children and adolescents in Finland in 1990-2014: nationwide re-evaluation of histopathological characteristics - Rousi Emma K.; Kallionpää Roope A.; Kallionpää Roosa E.; Juteau Susanna M.; Talve Lauri A.; Hernberg Micaela M.; Vihinen Pia P.; Kähäri Veli-Matti; Koskivuo Ilkka O. (TAYLOR & FRANCIS LTD, 2022)
Background
Changes in the incidence of melanoma in children and adolescents have been reported in Europe and in the USA in the recent decades.
Aims
The aim of this study was to examine the incidence of paediatric and adolescent melanomas in Finland in 1990-2014, and the associated clinical and histopathological characteristics to reveal temporal trends, such as changes in diagnostic sensitivity of Spitzoid melanomas.
Methods
Information on 122 patients diagnosed with cutaneous melanoma at 0-19 years of age in Finland in 1990-2014 were retrieved from the Finnish Cancer Registry. 73 primary melanoma archival samples were re-evaluated by two dermatopathologists to allow comparability over time.
Results
A 5.6% annual increase was observed in the incidence of melanoma among children and adolescents during the study period. Fifty-six tumours were confirmed as malignant melanomas in the re-evaluation. After correction for tumour misclassification in the Cancer Registry, the age-adjusted annual incidence was estimated to have increased from 1.4/1 000 000 in 1990-1994 to 5.8/1 000 000 in 2010-2014. The change in incidence was most prominent among adolescents and in Spitzoid melanoma subtype. Melanomas diagnosed 1990-2002 and 2003-2014 did not differ in terms of their clinicopathological characteristics or prognosis (hazard ratio for melanoma-related death 1.53, 95% CI 0.30 to 7.88). Spitzoid melanomas were diagnosed at a younger age, were of higher stage and had higher Clark level than other melanomas, yet the hazard ratio for death was 0.52 (95% CI 0.10 to 2.58) for Spitzoid versus other melanomas.
Conclusions
The incidence of cutaneous melanoma has clearly increased among the young in Finland, especially among adolescents. No evidence for overdiagnosis of Spitzoid melanomas as the underlying cause of the increased incidence was observed.
Key message
A nationwide retrospective re-evaluation of the cutaneous melanomas recorded in the Finnish Cancer Registry among patients aged 0-19 years in Finland in 1990-2014 revealed an approximately 4-fold increase in the incidence. The increase in the incidence was most prominent among adolescents and in the Spitzoid melanoma subtype. Our results contrast those reported in other countries, where the incidence of melanoma among adolescents has declined.